2020
DOI: 10.1186/s13068-020-1652-z
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid overproduction improves lignocellulose quantity and quality to maximize bioethanol yield under green-like biomass process in transgenic poplar

Abstract: Background: As a leading biomass feedstock, poplar plants provide enormous lignocellulose resource convertible for biofuels and bio-chemicals. However, lignocellulose recalcitrance particularly in wood plants, basically causes a costly bioethanol production unacceptable for commercial marketing with potential secondary pollution to the environment. Therefore, it becomes important to reduce lignocellulose recalcitrance by genetic modification of plant cell walls, and meanwhile to establish advanced biomass proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 64 publications
3
22
0
Order By: Relevance
“…Dried and milled poplar was used for analysis of sugar yield. Chemical pretreatment and sequential enzymatic hydrolysis were performed as described previously with minor modifications [45][46][47]. For H 2 SO 4 pretreatment: the well-mixed biomass samples were treated with 6 mL 4% H 2 SO 4 at 120 °C for 20 min, then shaken under 150 rpm at 50 °C for 2 h. For NaOH pretreatment: the well-mixed biomass samples were incubated with 6 mL 4% NaOH shaken at 50 °C for 2 h. After pretreatments, the pretreated residues were washed with distilled water for 3-5 times until pH 7.0 for following enzymatic hydrolysis.…”
Section: Chemical Pretreatment and Biomass Enzymatic Hydrolysismentioning
confidence: 99%
“…Dried and milled poplar was used for analysis of sugar yield. Chemical pretreatment and sequential enzymatic hydrolysis were performed as described previously with minor modifications [45][46][47]. For H 2 SO 4 pretreatment: the well-mixed biomass samples were treated with 6 mL 4% H 2 SO 4 at 120 °C for 20 min, then shaken under 150 rpm at 50 °C for 2 h. For NaOH pretreatment: the well-mixed biomass samples were incubated with 6 mL 4% NaOH shaken at 50 °C for 2 h. After pretreatments, the pretreated residues were washed with distilled water for 3-5 times until pH 7.0 for following enzymatic hydrolysis.…”
Section: Chemical Pretreatment and Biomass Enzymatic Hydrolysismentioning
confidence: 99%
“…Despite great progress in investigating PCW recalcitrance, few studies have compared the enzymatic digestibility of herbaceous and woody biomass by pathogenic fungi. Different woody and herbaceous biomass have distinguishable PCW compositions, polymer features, and structures [ 8 , 9 ]. For instance, substitutions on xylans, the major component of the secondary cell walls (SCWs) of dicotyledonous and grass plants, are diverse and vary phylogenetically [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, after 10% CaO pretreatment, the P. simonii sample showed the most reduction by 42%, resulting in the lowest cellulose DP value measured in the CaO pretreatment residue from P. simonii sample. Recent studies have indicated that reduced cellulose DP could provide more reducing ends of β-1,4-glucans for efficient enzymatic hydrolysis of lignocellulose in both grassy plants and woody plants (Alam et al, 2019;Cheng et al, 2018;Fan et al, 2020;Huang et al, 2015;Li et al, 2018), the most reduction on cellulose DP is consistent with the highest hexoses yield achieved in the P. simonii sample. To confirm this finding, we observed lignocellulose morphogenesis of two Populus species (P. simonii and P. deltoides) using scanning electronic microscopy (Figure 5b).…”
Section: Mechanism Of Enhanced Biomass Enzymatic Saccharification In P Simoniimentioning
confidence: 62%
“…Thus, selection of the desirable woody plants becomes a promising solution for mild and green‐like biomass pretreatment and efficient enzymatic saccharification toward cost‐effective bioethanol production. Furthermore, genetic modification of lignocellulose has been implemented to originally reduce recalcitrance in bioenergy woody plants (Fan et al., 2017, 2020; Huang et al., 2019; Li et al., 2018; Straub et al., 2019; Wang et al., 2016; Wu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%